Health literacy and post-vaccination COVID-19 prevention behavior in the community: a crosssectional study in Indonesia - Jon Hafan Sutawardana; Yofita Refvinda Desfiani; Nur Widayati (Universitas Airlangga, 2023)
Background: The government has made vaccination the primary strategy to control the COVID-19 pandemic. However, the public still needs to implement COVID-19 prevention behavior even though they have been vaccinated because COVID-19 infection with or without symptoms can still occur. Health literacy is the basis for behavior change. Purpose: This study aimed to determine the relationship between health literacy and post-vaccination COVID-19 prevention behavior of the community in the work area of